Exploring the diagnostic landscape of Mannheimia haemolytica: technologies, applications, and perspectives - Wang, Chenxiao; Bai, Xindong; Wang, Juan; Ye, Dongyang; Dou, Leina; Yang, Zengqi (Frontiers in Microbiology, 2025)
Mannheimia haemolytica (M. haemolytica) is recognized as a primary etiological agent of bovine respiratory disease (BRD) and ovine contagious pleuropneumonia. The clinical burden associated with these infections highlights the importance of early diagnosis to enable timely therapeutic interventions and prevent large-scale outbreaks. Conventional diagnostic approaches, including culture-based isolation and biochemical identification, remain standard practices for M. haemolytica detection, which enable recovery of complete bacterial isolates for downstream analyses. Recent advances in molecular diagnostics technology have dramatically improved the sensitivity, specificity, and turnaround time of M. haemolytica detection. Immunological assays, including enzyme-linked immunosorbent assays and agglutination tests, are important for high-throughput screening in epidemiological investigations. Additionally, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry has emerged as a valuable adjunct for the rapid, automated identification of M. haemolytica, further streamlining clinical workflows. While considerable progress has been made in diagnostic technologies for M. haemolytica, a comprehensive review of these methods remains lacking. Existing reviews largely focus on the broader BRD complex or pathogenesis, rather than systematically evaluating diagnostic strategies tailored to M. haemolytica. Therefore, we first to critically appraise and summarize recent developments in traditional, molecular, immunological, and mass spectrometric diagnostic techniques, providing a consolidated reference for early, accurate, and field-deployable detection of M. haemolytica infections.